System-dynamics-based scenario simulation and prediction of water carrying capacity for China - Liu, Bin (2022)
Water carrying capacity (WCC) is essential to support regional sustainable development. In this study, a nation-wide system dynamics model was developed to predict WCC of China for the near future period (2019–2030) based on system analysis of water resources and historical data from 2000 to 2018. The system dynamics model considers three water resources conditions (i.e., normal, wet, and dry) and four development modes (i.e., business-as-usual, priority-for-economy, environmental-constraint, and sustainable development) to holistically represent possible future conditions. From the prediction, the total population and GDP of China would continue growing under all scenarios, and the total wastewater discharge would generally rise first and then decline largely due to the growth of GDP per capita. The water supply-demand ratio would be greatly affected by development mode, depending on the combinative effects of population, GDP and water intake under each development mode. The impact of the wet condition on the modeling results is limited, but that of the dry condition is significant, especially on supply-demand ratio due to the limited water resources. From decision analysis, the four development modes have their own advantages. But from a long-term point of view, the sustainable development mode would outperform others due to its more balanced consideration. The study methodology and findings are valuable for assisting national or regional systems planning of water resources and water quality, especially in face of various challenges such as climate change, eco-environmental deterioration, and water resources shrinkage.